Executive behavior and functional abilities in children with perinatal stroke and the associated caregiver impact. Issue 1 (2nd January 2021) - Khan, Muhammad H.; Smithson, Lisa; Li, Eliza; Kirton, Adam; Pei, Jacqueline; Andersen, John; Yager, Jerome Y.; Brooks, Brian L.; Rasmussen, Carmen
ABSTRACT: Perinatal stroke is the most common form of stroke in childhood and is followed by a variety of outcomes, with many children experiencing specific functional and neuropsychological deficits. The association of these outcomes with the psychosocial impact caregivers face is not well documented. The goal of our pilot study was to examine caregivers' perception of executive behavior and functional abilities among children with perinatal stroke, and how these outcomes impact the caregivers. We administered three questionnaires to primary caregivers of children with perinatal stroke to obtain caregiver-reported measures of (1) executive behavior of their child (Behavior Rating Inventory of Executive Function, Second Edition), (2) the functional abilities of their child (Pediatric Evaluation of Disability Inventory Computer Adaptive Test), and (3) the psychosocial impact experienced by the caregiver themselves (Parental Outcome Measure). Participants included 20 children (mean age = 9.3 years, range = 6–16 years) with perinatal stroke and their primary caregivers. Functional abilities in the children were rated as clinically impaired in the domains of daily activities and mobility. Half of the children exhibited clinically impaired ratings on at least one executive behavior domain, but the mean scores for these domains did not reach clinically impaired levels. Greater ratings of problems in daily activities for the child was associated with greater caregiver guilt ( r = −0.55, p = 0.02). Caregivers of children with perinatal stroke who experience limitations in performing daily activities should be more closely monitored for adverse impact and be provided the necessary support and education to alleviate the associated guilt.